Sealing - Treatment Repair Technology of Cast Magnesium Alloy Shell Parts - NAN Jian, DAI Xue - ting (Cailiao Baohu, 2021)
Due to the various degrees of internal defects (e.g. shrinkage, corroded points) in cast magnesium alloy shell, the fluid is easy to leakage. This kind of leakage has the characteristics of small leakage, many leakage points and difficulties to accurate locating position. Therefore, it is hard to solve the problem with welding technology. For this, in this work, the cast magnesium alloy with the same material as the generator was used to make the sample. The self - made sealant and method of brushing coating were used to seal the hole. Meanwhile, the technological process was established combining with the characteristics of the products. Results showed that higher surface roughness of samples could make the better bonding between sealant and matrix. The samples after sealing had good oil resistance and corrosion resistance. The verification experiment on the generator shell proved that the property of cast magnesium alloy shell after sealing could meet the requirements of real usage. This optimized process was easy to operate and could meet the quality requirements of products. This process could be directly applied to sealing - treatment of cast magnesium alloy shell in special environment, indicating the good economic benefit, quality benefit and application prospect of technology.